Simulation of Thermal Load of A Restaurant’s Building at Sebha City to Which Simple Passive Techniques Were Applied - Omar Ahwidi , Gassem Azzain (Journal of Pure & Applied Sciences, 2020)
The simulation of possible heating and cooling requirements of restaurant's building has been presented in this paper, when simple Thermal Passive Techniques (TPT) such as Building materials selection, Insulation, and careful design of the doors and windows have been applied to building’s construction in Sebha city at the Libyan south. The known software for dynamic simulations (TRNSYS 16) has been used as an environment of digital experimentation for this study. A model represents the building has been constructed with the help of the available model of the Multi-zone Building modeling with Type56 and TRNBuild. The thermal load on building’s construction with TPT (such as the control of building materials, insulation, shading, infiltration and ventilation with window resizing) has been calculate under weather conditions of a Typical Meteorological Year (TMY) of Sebha city . The simulation has been conducted successfully, where good result of heating and cooling demands during JAN month of the building has been obtained. The maximum about (21571 KJ/hr) of heating load for dining room, (34 KJ/hr) of heating load for kitchen, (12046 KJ/hr) of cooling load for kitchen and didn’t has any thermal load for storage room.